Case report: Development of vanishing bile duct syndrome in Stevens-Johnson syndrome complicated by hemophagocytic lymphohistiocytosis - Lin, Wan-Chen; Hsieh, Tyng-Shiuan; Chu, Chia-Yu (Frontiers in Medicine, 2022)
Background: Vanishing bile duct syndrome is a rare drug-induced disease characterized by cholestasis and ensuing ductopenia. Dermatological manifestations of drug hypersensitivity such as Stevens-Johnson syndrome and toxic epidermal necrolysis may also present in such cases. Hemophagocytic lymphohistiocytosis is a hyperimmune response caused by unchecked stimulation of macrophages, natural killer cells, and cytotoxic T lymphocytes. Case presentation: We report a severe case who presented with concurrent Stevens-Johnson syndrome and vanishing bile duct syndrome complicated by hemophagocytic lymphohistiocytosis after the ingestion of non-steroidal anti-inflammatory drugs. Despite the fact that improvement of vanishing bile duct syndrome could be assumed when combining clinical clues of initially significant decrease in liver enzymes and bilirubin levels after steroid treatment and the repeat liver biopsy, which showed ductopenia in recovery, the patient developed hypovolemic shock combined with septic shock episodes and died on day 236. Conclusion: To our knowledge, this is the eleventh report of vanishing bile duct syndrome associated with Stevens-Johnson disease or toxic epidermal necrolysis. Mortality rate remains high without treatment guidelines established due to the rarity and heterogenicity of the population. Further studies are needed to identify possible risk factors, prognostic indicators, and the standard of care for vanishing bile duct syndrome associated with Stevens-Johnson disease or toxic epidermal necrolysis.